1997
DOI: 10.22358/jafs/69508/1997
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of meatness traits in six generations of ducks in conservative groups

Abstract: In 6 generations of ducks from 4 conservative groups: Khaki Campbell (Khl), Orpington (01), their crosses (KhOl) and Miniducks (K2), mean values of some meatness traits, their coefficients of variation (v, v years ) and repeatability (r p ) were estimated. Live weight of the 7-week-old birds and contents of the investigated tissue components in the carcass differed depending on the origin and sex of the birds. In all groups, lower v and v ycars values of live weights in the 3rd and 7th week of life were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…In Poland, the idea of conserving and protecting the genetic resources of ducks dates back to the early 1970s [13,15]. The conservation flocks of ducks, which since 1977 were maintained without selection using the in situ method, are source of genetic variation and were used to create new breeding strains, experimental strains or synthetic groups [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, the idea of conserving and protecting the genetic resources of ducks dates back to the early 1970s [13,15]. The conservation flocks of ducks, which since 1977 were maintained without selection using the in situ method, are source of genetic variation and were used to create new breeding strains, experimental strains or synthetic groups [15].…”
Section: Introductionmentioning
confidence: 99%
“…This programme contains the history of the breed, justifies the need to protect individual flocks of ducks, and specifies flock standards, programme objectives, the scope of productive value evaluation and breeding methods used [15]. In recent years, ducks raised at the Waterfowl Station in Dworzyska have received considerable study [13,14,19,23,24]. P11, P22, P44 and P55 ducks (Duck Breeding Centre in Lińsk) were the subject of few studies many years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to management of birds in conservative or genetic reserve flocks, their genetic variation and yet undetected markers of different traits can be preserved. Conservative flocks of ducks conserved in situ are a source of genetic variation, which is, among others, a condition of further breeding work (KSIĄŻKIEWICZ and MAZANOWSKI, 1984). The world's genetic resources conservation programme (World Watch List -FAO, 2000) includes two Polish duck populations -Miniducks (K2) and Pekin ducks (P33).…”
Section: Introductionmentioning
confidence: 99%
“…Dressing percentage of P8 ducks was greater than that obtained by Książkiewicz (1997) for the same population and greater than that of Pekin ducks from Hungary, Germany, Russia and the Czech Republic tested in Ivanka on the Danube (Evaluation, 1989). Staško (1990) reported that at 10 weeks in males and 8 weeks in females in the crosses of Khaki Campbell, wild mallard and Pekin ducks, dressing percentage reached up to 74% on average.…”
Section: Discussionmentioning
confidence: 55%
“…It follows current international trends in methods of managing such flocks (Fujihara and Xi, 1999). Previous studies have described national duck populations in terms of reproductive and meat traits (Książkiewicz, 1997(Książkiewicz, , 2002 and taken a dynamic view of changes in reproductive traits over 8 generations (Książkiewicz and Kiełczewski, 1998) or in meat traits over 10 generations of conservative ducks (Książkiewicz, 2002). In Polish Pekin (P33) and Miniducks (K2) differences were shown for chemical composition of meat , while Książkiewicz et al (1999) confirmed the influence of bird origin on physical properties and quality traits of eggs.…”
Section: Introductionmentioning
confidence: 99%